The utility of knowledge sources about upbringing according to small children mothers’ opinions - Szymanik-Kostrzewska, Anna; Michalska, Paulina (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2018)
The purpose of presented research was to define utility of resource knowledge about children upbringing. The Sources of Knowledge about Upbringing Questionnaire, constructed by authors, was used. In voluntary, anonymous tests took a part 260 mothers having at least one child in the age between 1–7 years old. They determined the utility of chosen knowledge resources. According to mothers the most useful knowledge resource about upbringing are instinct and their personal feelings, next to opinions about their child formulated by representatives with medical education (doctors, nurses) and their own experience from childhood. Mothers recognized public statements of media representatives (e.g. celebrities), who does not possess professional knowledge about upbringing, as the least useful source. The statements about children coming from unknown Internet representatives turned out to be very unhelpful as well.
Keywords: upbringing; knowledge about upbringing; small children